Innovation in Urban and Regional Planning
XVII, 663 p. 180 illus., 157 illus. in color.
Keywords: This book gathers the latest advances, innovations, and applications in urban and regional planning processes and science, as presented by international researchers at the 11th International Conference on Innovation in Urban and Regional Planning (INPUT), held in Catania, Italy, on September 8-10, 2021. The overarching theme of the conference INPUT 2021 was “Integrating Nature-Based Solutions in Planning Science and Practice”, with contributes focusing on functionality of urban ecosystems toward more healthier and resilient cities, planning solutions for socio-ecological systems, technologies and hybrid models for spatial planning, geodesign, urban metabolism, computational planning, ecosystems services, green infrastructure, climate change adaptation and mitigation, rural landscapes, cultural heritage, and accessibility for urban planning. The conference brought together international scholars in the field of planning, civil engineering and architecture, ecology and social science,to build and consolidate the knowledge and evidence on NBS in urban and regional planning.